The Accuracy of Matching Target Insertion Gains With Open-Fit Hearing Aids. - Aazh, Hashir; Moore, Brian C. J.; Prasher, Deepak (American Journal of Audiology, 2012)
Purpose: To assess the accuracy with which target insertion gains were matched for a single type of open-fit hearing aid, both on initial fitting and after adjustment. Method: The hearing aids were fitted using the first-fit setting in the programming software and the target formula was selected as NAL-NL1. The difference between the real ear insertion gain (REIG) and the NAL-NL1 target REIG was recorded. The initial fitting was considered acceptable if the difference was less than 10 dB at all frequencies. If an initial fitting was not acceptable, the frequency-gain response was modified. The difference between the final REIG and the NAL-NL1 target REIG was recorded as final target mismatch. Results: Of the 51 initial fittings, 36 (71%) failed to achieve a match within ±10 dB of the NAL-NL1 insertion gain target at 1 or more frequencies between 0.25 and 4 kHz. After the authors adjusted the frequency-gain response of the hearing aids, only 9 fittings (18%) failed to achieve a match. Conclusion: These outcomes suggest that target insertion gains for the open-fit hearing aids used here are rarely achieved with a first fitting but can usually be achieved through adjustments based on REIG measurements.